The Diet and Sexual Differences of the Caspian Bent-Toed Gecko, Tenuidactylus caspius (Squamata: Gekkonidae), in Northern Iran - Hojati, Vida; Babaei Savasari, Reza (International Journal of Zoology, 2014)
The Caspian bent-toed gecko, Tenuidactylus caspius, is one of the most common nocturnal lizards of Iran with widespread distribution especially in the northern provinces. This research was done in order to study the diet and sexual dimorphism of this species in Sari County from 5 May to 20 October. During this research, 40 specimens of them including 20 males and 20 females were studied for diet and 140 specimens including 70 adult males and 70 adult females were studied for sexual dimorphism. Prey items identified were insects that belong to 15 species of 8 families and 6 orders. The most common prey items were Culex pipiens and Musca domestica. There is no significant difference between diets of males and females. Results show that the adult males in addition of having the apparent femoral and preanal pores are heavier than females and have larger body, head, and tail length.